The Influence Between Government Expenditure Towards Poor Resident in Indonesia - Miftakhul Khasanah; Prasetyo Ari Wibowo (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2016)
The purpose of this study is to find out how much is the influence of the government’s expenditure on the function of health, education, housing and public facilities in Indonesia during 2008-2013. The sample of this study were the government’s expenditure on the function of health, education, housing and public facilities as well as the number of poor residents in Indonesia during 2008-2013. The collected data was analyzed using quantitative method. This study used panel data regression analysis with 95% significance (α=5%). The result of the analysis on t test and F test showed that all of the independent variables were influential towards the dependent variables. The suggestion corresponding to the result of this study are (1) The government should adjust the budget allocation for health function by 10% (2) the government should adjust the budget allocation for education function by 20% (3) there should be development in housing sector which is in favor of the poor residents (pro poor).